Artificial musculoskeletal actuation module driven by twisted and coiled soft actuators. (8th November 2019) - Cho, Kyeong Ho; Kim, Youngeun; Yang, Sang Yul; Kim, Kihyeon; Park, Jae Hyeong; Rodrigue, Hugo; Moon, Hyungpil; Koo, Ja Choon; Nam, Jae-do; Choi, Hyouk Ryeol
Abstract: Skeletal muscles produce contractile motions and a couple of skeletal muscles antagonistically arranged are required to create bidirectional active movements. The musculoskeletal system is mainly composed of two skeletal muscles, joint, bones and tendons, and thus, a joint performs active bidirectional rotations. Likewise, twisted and coiled soft actuator (called TCA in this study) exhibits only unidirectional actuation, and two TCAs in antagonistic structure can produce bidirectional active motions. However, the TCA exhibits characteristics similar to that of tension coil spring, and it diminishes the available force and displacement from two TCAs in the antagonistic structure. In this study, a dual spiral pulley is proposed to overcome the limitations of TCAs. In the first, the artificial musculoskeletal actuation module (AMAM) is fabricated by integrating two spandex-based TCA (called STCA in this paper) bundles with the dual spiral pulley. The AMAM is experimentally tested, and its feasibility is validated. In addition, a robotic arm was developed with the AMAM, and successfully demonstrated full biceps curl and triceps kickback motions.